The Practical Teaching Activities in Preparing the Potential of Female Students to Become Ustadzah - Hilmi, Wildan Aqiel; Sulaeman, Maryam; Fauzi, Anas; Makhisoh, Iis; Hasbullah, Abdur Rouf (IERA, Islamic Education and Research Academy, 2024)
This study was conducted to examine the implementation of flashcards in Arabic language learning to enhance vocabulary acquisition interest among eighth-grade students at MTs Darul Muta'allimin Patianrowo. The objectives of this study are to describe the use of flashcards in Arabic language instruction, assess student interest in vocabulary learning, and evaluate the effectiveness of flashcards in improving learning outcomes. This research employs a qualitative approach, using data collection techniques such as interviews, observations, and documentation. The findings indicate that the use of flashcards in Arabic language learning was effective, as it facilitated students' understanding of the material. Supporting factors for this success include competent teachers, appropriate teaching media, adequate facilities, high student motivation, and a conducive learning environment. However, several challenges were identified, such as differences in educational backgrounds, diverse student characteristics, varying abilities, and fluctuating levels of motivation. Overall, the use of flashcards significantly increased student interest and engagement in vocabulary learning. This suggests that flashcards can be an effective tool to strengthen students' understanding and interest in mastering Arabic vocabulary